Мифы, легенды и сказки удмуртского народа - Кралина Надежда Петровна (Удмуртия, 2019)
Экземпляры: аб. ЦБ (20200818) / Инвентарный номер: 7924 / Цена: / Сис.шифр: 82.3(2) / Авт.знак: М 68 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм).06